Relevance of Aceh's Qanun Jinayat in Minimizing Cases of Sexual Harassment against Children in Aceh - Wiwin Widiarti; Erika Magdalena Chandra; Rully Herdita Ramadhani (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to describe the relevance of Qanun Number 6 of 2014 concerning Jinayat Law as a legal regulation used to address cases of child sexual Harassment in Aceh. This is considered important because until now cases of child sexual Harassment in Aceh have continued to increase every year. In addition, Aceh is a region that has special regulations that are formed based on Islamic law and customary law. Therefore, the provisions relating to sexual Harassment in Aceh are different from other provincial areas that use the Child Protection Law, the Sexual Violence Crime Law or Law Number 1 of 2023 concerning the Criminal Code. The study was conducted using a sociological legal research method with descriptive analytical writing specifications. The focus of this study is on how the relevance of Aceh Qanun Number 6 of 2014 concerning Jinayat Law is in minimizing the number of cases of child sexual Harassment in Aceh, thus causing this study to be different from previous studies. The results of this study indicate that Qanun Number 6 of 2014 concerning Jinayat Law has not been able to optimally address cases of child sexual Harassment in Aceh. It is because the five factors that influence the effectiveness of the implementation of Qanun Jinayat in Aceh have not been effective until now. The five factors are legal factors, law enforcement factors, facilities and infrastructure factors, community factors and cultural factors. In addition, the provisions of the threat of sanctions contained in Qanun Jinayat when associated with the theory of just desert and the theory of the purpose of punishment in Islamic criminal law are still relatively light so that they have an impact on the unprotection of children's rights as victims and do not provide a deterrent effect for perpetrators.